Clinical correlates of grey matter pathology in multiple sclerosis - Horakova, Dana; Kalincik, Tomas; Dusankova, Jana Blahova; Dolezal, Ondrej (BMC neurology, 2012)
Traditionally, multiple sclerosis has been viewed as a disease predominantly affecting white matter. However, this view has lately been subject to numerous changes, as new evidence of anatomical and histological changes as well as of molecular targets within the grey matter has arisen. This advance was driven mainly by novel imaging techniques, however, these have not yet been implemented in routine clinical practice. The changes in the grey matter are related to physical and cognitive disability seen in individuals with multiple sclerosis. Furthermore, damage to several grey matter structures can be associated with impairment of specific functions. Therefore, we conclude that grey matter damage - global and regional - has the potential to become a marker of disease activity, complementary to the currently used magnetic resonance markers (global brain atrophy and T2 hyperintense lesions). Furthermore, it may improve the prediction of the future disease course and response to therapy in individual patients and may also become a reliable additional surrogate marker of treatment effect.
Keywords: mozková kůra; Cerebral Cortex; Inflammation; roztroušená skleróza; lidé; Disease Progression; atrofie; Humans; progrese nemoci; mozek; Brain; kognitivní poruchy; Cognition Disorders; Multiple Sclerosis; Atrophy; zánět